Educational Communities of Inquiry 2013
DOI: 10.4018/978-1-4666-2110-7.ch004
|View full text |Cite
|
Sign up to set email alerts
|

From Distance Education to Communities of Inquiry

Abstract: The purpose of this chapter is to explain the role and place of the Community of Inquiry (CoI) framework within the history of distance education. The review of the history reveals two important factors for changes in distance education: the effect of leading learning theories of each era and technological advancements. Distance education has moved from a behavioristic, teacher–centered, correspondence study concept, first to an independent learning model, and then to the current student-centered, socio-constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Some teachers characterized themselves as guides to help students obtain resources; others sought approaches to sustain student interaction. In doing so, these findings resonate with those of Ahn (2011), Ko and Rossen (2017), Moore (2007), and Tolu and Evans (2013) who found that approaches used in face-to-face settings often need extensive modification to fit online environments. Time also factored into stated needs to develop contingency plans for technology failure.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Some teachers characterized themselves as guides to help students obtain resources; others sought approaches to sustain student interaction. In doing so, these findings resonate with those of Ahn (2011), Ko and Rossen (2017), Moore (2007), and Tolu and Evans (2013) who found that approaches used in face-to-face settings often need extensive modification to fit online environments. Time also factored into stated needs to develop contingency plans for technology failure.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, resources taken for granted in K-12 settings (e.g., technology support, reliable internet, scientific probes, art supplies) may be less available in individual homes. Likewise, a teacher's ability to ascertain students' engagement, understanding, and on-task behavior by scanning the classroom is hampered dramatically (Tolu & Evans, 2013;Zhan & Mei, 2013). To compensate for physical distance, caregivers often assume greater responsibility for personal coaching, resource acquisition, and motivation (Ahn, 2011;Borup et al, 2020;Hasler-Waters et al, 2014;Miron & Urschel, 2012).…”
Section: Changing Rolesmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials and the course structure must be created with a keen awareness of the characteristics of the student population, and systematic organization and deployment: “in distance education teaching is hardly ever an individual act, but a collaborative process joining together the expertise of a number of specialists in design teams and delivery networks” (Moore, 1993: 28). Existing studies found that teaching presence in the form of course design and organization, facilitation and instruction (Akyol and Garrison, 2008), and presence of communities of inquiry can reduce transactional distance in an online and/or blended environment (Tolu and Evans, 2013). Creating and sustaining online learning communities leads to “a shift from an environment characterized by novelty and uncertainty (due to technology) to one of belonging and familiarity” (Gigliotti, 2016: 409).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, the CoI is founded on social learning and social constructivism, collaborative learning and instructional design, and distance education (Tolu & Evans, 2013). Its constructivist feature shares Vygotsky's vision regarding the function of language and discourse as a way to construct meaning (Wells, 2000).…”
Section: The Community Of Inquiry Frameworkmentioning
confidence: 99%